(untitled) (Journal of Nepal Geological Society, 1982)
Results of recent geological mapping in the region of the Main Central Thrust of central Nepal indicate that the Benighat Slates and overlying units are a nappe probably equivalent to the Jutogh Group of Kumaon. Interpretation of the Ampipal Nepheline Syenite as basement of the Indian Shield implies that the Lower Nawakot Group is also a nappe. Total displacement on the Benighat Nappe, the Lower Nawakot Nappe and the previously described Kathmandu Nappe exceeds 210 km, indicating that continental crust of the Indian Plate has underthrust southern Tibet. South of the Transhimalayan magmatic arc, loss of the former arc-trench gap implies more than 100 km of northward overthrusting by upper crustal rocks of the Tethyan Himalayas.